A case report of primary cardiac angiosarcoma with DNMT3A gene mutation - Tian, Kun; Liu, Yating; Zhu, Haiying; Wang, Tao; Chen, Tianxing; Pei, Xiaxia; Song, Feixue (Frontiers in Oncology, 2022)
Cardiac angiosarcoma is a rare disease with a high mortality rate despite its low incidence. Surgery is currently the mainstay treatment strategy for patients with this condition. Herein, we describe a case of primary cardiac angiosarcoma, including symptoms, examination findings, treatment strategy and prognosis. In 2020, the patient was admitted to our hospital, and Next-Generation Sequencing (NGS) revealed a mutation in the DNMT3A gene. Generally, DNMT3A mutations are most commonly seen in atherosclerosis and myeloid leukemia. To our knowledge, this is the first reported case of primary cardiac angiosarcoma with DNMT3A gene mutation.